Cave Microbiomes: A Novel Resource for Drug Discovery - Cheeptham, Naowarat (Springer New York : Imprint: Springer, 2013)
This book details recent findings in the field of cave microbiology and builds on fast-paced efforts to exploit an unconventional and underexplored environment for new microorganisms which may provide an untapped source of drugs: microorganisms from caves.